The Role of Digital Media in Forming Islamic Character of Students of Elementary School - Ma’mur, Masbur; Abidin, Zaenal; Basarah, Muhamad Ali (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Amidst the rapid development of information technology, the existence of digital platforms has become an inherent part of the dynamics of children's lives, including elementary school students. Ideally, these technology-based tools are expected to be a bridge for the internalization of Islamic values through educational content with religious nuances. However, the reality in the field shows that the use of these media is often unfocused, tending towards entertainment consumption that does not provide significant benefits. This condition raises concerns regarding its negative influence on the formation of Islamic morality in children. This study seeks to explore the variety of digital platforms used by elementary school students in their daily activities and understand their contribution to shaping Islamic character. The approach used is a library research method with thematic analysis to explore relevant academic sources. The results of the study revealed that elementary school students generally use internet-based short video applications and online education platforms as the main medium. In addition, digital media has great potential as a vehicle for internalizing Islamic values if used wisely. The recommendation given is the need for assistance from parents and educators in selecting and directing the use of digital media towards holistic development goals